A Thermal and Enzymatic Dual‐Stimuli Responsive DNA‐Based Nanomachine for Controlled mRNA Delivery. Issue 4 (3rd December 2022) - Li, Feng; Sun, Xiaolei; Yang, Jing; Ren, Jin; Huang, Mengxue; Wang, Shengqi; Yang, Dayong
Abstract: The extreme instability of mRNA makes the practical application of mRNA‐based vaccines heavily rely on efficient delivery system and cold chain transportation. Herein, a DNA‐based nanomachine, which achieves programmed capture, long‐term storage without cryopreservation, and efficient delivery of mRNA in cells, is developed. The polythymidine acid (Poly‐T) functionalized poly( N ‐isopropylacrylamide) (DNA‐PNIPAM) is synthesized and assembled as the central compartment of the nanomachine. The DNA‐PNIPAM nano‐assembly exhibits reversible thermal‐responsive dynamic property: when lower than the low critical solution temperature (LCST, ≈32 °C) of PNIPAM, the DNA‐PNIPAM transforms into extension state to expose the poly‐T, facilitating the hybridization with polyadenylic acid (Poly‐A) tail of mRNA; when higher than LCST, DNA‐PNIPAM re‐assembles and achieves an efficient encapsulation of mRNA. It is remarkable that the DNA‐PNIPAM nano‐assembly realizes long‐term storage of mRNA (≈7 days) at 37 °C. Biodegradable 2‐hydroxypropyltrimethyl ammonium chloride chitosan is assembled on the outside of DNA‐PNIPAM to facilitate the endocytosis of mRNA, RNase‐H mediating mRNA release occurs in cytoplasm, and efficient mRNA translation is achieved. This work provides a new disign principle of nanosystem for mRNA delivery. Abstract : A thermal and enzymatic dual‐stimuli responsive DNA‐based nanomachine by using dynamic assembly of polymer framework and hybridization between DNA and mRNA is reported, achieving programmed capture and release, long‐term storage without cryopreservation, and efficient delivery of mRNA in cells. This work provides a new design principle of nanosystem for mRNA delivery.